Double heterozygocity for hemoglobin C and beta thalassemia dominant: A rare case of thalassemia intermedia - Alexandra Agapidou; Paul King; Cecilia Ng; Dimitris A. Tsitsikas (Hematology Reports, 2018)
Beta thalassemia dominant results from mutations in the β globin chain gene resulting in the production of elongated, highly unstable beta globin chains. Several such mutations have been described and in a heterozygous state they may confer a phenotype more severe than that of β thalassemia trait and lead to a clinical syndrome of thalassemia intermedia and its associated complications such as extramedullary hemopoiesis, bone disease, endocrinopathies and iron overload even in the absence of transfusion. In this report we present a case of double heterozygocity for HbC and β thalassemia dominant leading to a series of complications that were treated successfully once the correct diagnosis was made.